THE EFFECTIVENESS OF USING VIRTUAL EXPERIMENTS ON ENHANCING STUDENTS' LEARNING AND CREATIVITY IN GENERAL PHYSICS LABORATORY (World Bulletin of Social Sciences, 2024)
This article is devoted to studying the problem of using virtual reality technologies when conducting physics lessons. The work shows the possibility of creating a demonstration physical laboratory using new technologies. An analysis of the use of virtual reality in education is carried out, the main advantages and disadvantages are highlighted. Arguments are given in favor of the use of multimedia technologies in the education system. Virtual reality is a convenient tool for conducting scientific experiments when studying certain subject areas of physics that are difficult to consider in reality